Produção e caracterização de sistemas vítreos de boratos de magnésio para aplicação em dosimetria - Barrera, Gerardo Rivera (2019)
In this work, magnesium borate glasses with different concentrations were synthesized, resulting in the matrix systems: 80% MgB2O4 and 20% MgB4O7 (80MgB2O4-20MgB4O7) (mass%) and 60% MgB2O4 and 40% MgB4O7 (60MgB2O4-40MgB4O7). The glass samples were produced by the melting and rapid cooling method. The samples were doped with Ce (CO3)2, in the proportion of 0.1% to 0.9% to the total mass of compounds. Li2CO3 co-dopant was added to the matrix at a ratio of 0.1% to the total mass of 80MBO and 60MBO.The structural characterization of borate glasses was performed by X-ray diffraction (XRD), absorption spectroscopy techniques. UV-Vis and photoluminescence (PL). The XRD results have confirmed the amorphous nature of the investigated glasses, and UV-Vis spectra showed a tendency to increase the wavelength cut-off due to the addition of Ce3+, which can be associated to some structural alteration. The dosimetric characterization was carried out by the thermoluminescence (TL) and optically stimulated luminescence (OSL) technique.TL and OSL characteristics of the glasses were evaluated, such as glow curve, dose-response curve, sensitivity, linearity and energy dependence, after exposure of the samples to ionizing radiation (x-rays and gamma radiation). The dose response curves TL and OSL of the glasses showed a linear behavior in the studied dose range (0.25 to 1.0 Gy). Among the studied doped magnesium borate glasses, those with the highest concentration of Ce3+ (0.9%), co-doped with 0.1% Li, exhibited the highest TL and OSL sensitivities. The results of this work confirm the possibility of using these glasses in dosimetry.